2005
DOI: 10.1002/art.20983
|View full text |Cite
|
Sign up to set email alerts
|

Pregabalin for the treatment of fibromyalgia syndrome: Results of a randomized, double‐blind, placebo‐controlled trial

Abstract: Results. Pregabalin at 450 mg/day significantly reduced the average severity of pain in the primary analysis compared with placebo (؊0.93 on a 0-10 scale) (P < 0.001), and significantly more patients in this group had >50% improvement in pain at the end point (29%, versus 13% in the placebo group; P ‫؍‬ 0.003). Pregabalin at 300 and 450 mg/day was associated with significant improvements in sleep quality, fatigue, and global measures of change. Pregabalin at 450 mg/day improved several domains of health-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
351
3
40

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 595 publications
(411 citation statements)
references
References 36 publications
17
351
3
40
Order By: Relevance
“…It is demonstrated that all these medications can positively influence sleep [58][59][60][61][62]. Duloxetine and milnacipram delay the onset and reduce the duration of REM sleep, improving sleep continuity and quality [63].…”
Section: Us Food and Drug Administration And The European Medicinesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is demonstrated that all these medications can positively influence sleep [58][59][60][61][62]. Duloxetine and milnacipram delay the onset and reduce the duration of REM sleep, improving sleep continuity and quality [63].…”
Section: Us Food and Drug Administration And The European Medicinesmentioning
confidence: 99%
“…Duloxetine and milnacipram delay the onset and reduce the duration of REM sleep, improving sleep continuity and quality [63]. Pregabalin has beneficial effects on pain, fatigue and quality of sleep [58]. Sleep improvement could be direct or due to the reduction in pain or both [59,62,64].…”
Section: Us Food and Drug Administration And The European Medicinesmentioning
confidence: 99%
“…Other benefits included improvement in sleep quality and fatigue. 89 Pregabalin is the newest available anticonvulsant and it has clearly been shown to be an effective analgesic.…”
Section: Pregabalinmentioning
confidence: 99%
“…It should also be possible to treat the pain and see the depression improve or vice versa. That did not happen when effective analgesics for central sensitization-related pain [but lacking antidepressant activity] were used to treat patients with FMS (8,9). Depression emerged or persisted unchanged despite significant relief of the chronic pain.…”
Section: The Role Of Depression In Chronic Musculoskeletal Painmentioning
confidence: 99%